2020
DOI: 10.2196/19975
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Attitudes of Adolescents and Young Adults Towards JUUL: Computational Study Using Twitter Data

Abstract: Background Increases in electronic nicotine delivery system (ENDS) use among high school students from 2017 to 2019 appear to be associated with the increasing popularity of the ENDS device JUUL. Objective We employed a content analysis approach in conjunction with natural language processing methods using Twitter data to understand salient themes regarding JUUL use on Twitter, sentiment towards JUUL, and underage JUUL use. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…Therefore, we find it necessary to understand tobaccorelated discussions and public sentiment to help shape better policies aimed at bio-surveillance and tobacco control measures. Previous research (Benson et al, 2020;Pant et al, 2019) in sentiment analysis, and topical tobacco research is heavily reliant on manually annotated datasets. These pose several challengesexpensive to make, limited in scope, difficult to modify, and harder to scale.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we find it necessary to understand tobaccorelated discussions and public sentiment to help shape better policies aimed at bio-surveillance and tobacco control measures. Previous research (Benson et al, 2020;Pant et al, 2019) in sentiment analysis, and topical tobacco research is heavily reliant on manually annotated datasets. These pose several challengesexpensive to make, limited in scope, difficult to modify, and harder to scale.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in popularity is largely attributable to the emergence of pod mods, ENDS devices with sleek designs that mimic the nicotinic delivery of combustible cigarettes (17,18). Although adults commonly use ENDS devices to aid in smoking cessation (6), studies have suggested that adolescents and young adults may be using ENDS devices recreationally rather than to aid smoking cessation (19,20). Further, a recent study demonstrated that from 2014 to 2018, the adolescent age of initiation for ENDS devices continued to decrease (21), meaning that adolescents were beginning ENDS use at younger ages.…”
Section: Ends Use In the United Statesmentioning
confidence: 99%
“…For their Tweet sentiment analysis, positive sentiment indicates users' intention to use, the act of using, or sequel from use. Benson et al ( 2020 ) investigated sentiment surrounding JUUL (i.e., an electronic nicotine delivery system) and vaping among youth and young adults by applying Logistic Regression, Naïve Bayes, and Random Forest for the detection of JUUL use and sentiment analysis. The Random Forest classifier achieved the best performance with 91% average detection accuracy among these classifiers.…”
Section: Related Workmentioning
confidence: 99%